Development of non-dairy probiotic beverages with Saccharomyces boulardii: current situation and perspectives (Research, Society and Development, 2020)
Probiotics are live microorganisms that, when administered in an adequate amount, confer benefit on the health of the host. Among the microorganisms usually used as probiotics, Saccharomyces boulardii is a highlight. Initially isolated from lychees, S. boulardii is a probiotic yeast usually used as a medicine to treat intestinal disorders. Fruits and vegetables, despite being rich in various nutrients beneficial to health, are not normally used as vehicles for probiotic microorganisms. Beverages based on fruits and/or vegetables are suitable as a matrix for the development of probiotic products because they do not contain dairy allergens that make it impossible for the population. In this review, studies are presented that point to the potential application of S. boulardii as a probiotic culture, in association with other microrganisms or nto, for addition in fruit and/or vegetable juices, by means of matrix and/or process adjustments, aiming at increasing scale and making this process economically viable.